2021
DOI: 10.1038/s42005-021-00628-x
|View full text |Cite
|
Sign up to set email alerts
|

Why reducing the cosmic sound horizon alone can not fully resolve the Hubble tension

Abstract: The mismatch between the locally measured expansion rate of the universe and the one inferred from the cosmic microwave background measurements by Planck in the context of the standard ΛCDM, known as the Hubble tension, has become one of the most pressing problems in cosmology. A large number of amendments to the ΛCDM model have been proposed in order to solve this tension. Many of them introduce new physics, such as early dark energy, modifications of the standard model neutrino sector, extra radiation, primo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(103 citation statements)
references
References 50 publications
6
96
0
1
Order By: Relevance
“…Such models are favoured by trying to simultaneously fit the SH0ES measurement of H 0 and the angular size of the sound horizon measured with Planck and BAO. Jedamzik et al (2021) show that the S 8 implied by Planck in such models is several sigma away from that measured by lensing (a similar result was found in the context of Early Dark Energy models in Hill et al 2020). This can be understood by noting that S 8 ∝ A 0.…”
Section: Appendix B: Weak Lensing + Bbn As a Standard Ruler Calibratorsupporting
confidence: 79%
See 1 more Smart Citation
“…Such models are favoured by trying to simultaneously fit the SH0ES measurement of H 0 and the angular size of the sound horizon measured with Planck and BAO. Jedamzik et al (2021) show that the S 8 implied by Planck in such models is several sigma away from that measured by lensing (a similar result was found in the context of Early Dark Energy models in Hill et al 2020). This can be understood by noting that S 8 ∝ A 0.…”
Section: Appendix B: Weak Lensing + Bbn As a Standard Ruler Calibratorsupporting
confidence: 79%
“…As the main focus of this paper is a study of how H 0 may be constrained with lensing, we believe our omission of the eBOSS DR16 data is justified. 13 As shown in Jedamzik et al (2021), galaxy lensing can help to constrain models with high Ω m h 2 (and hence low sound horizon) if one is willing to combine Planck primary CMB measurements and cosmic shear in a joint analysis. Such models are favoured by trying to simultaneously fit the SH0ES measurement of H 0 and the angular size of the sound horizon measured with Planck and BAO.…”
Section: Appendix B: Weak Lensing + Bbn As a Standard Ruler Calibratormentioning
confidence: 99%
“…The continued increase in expansion velocity involving a decline in microstates might be validated by the use of more powerful telescopes to determine whether the density of matter at the cosmic horizon exceeds the predicted value based on current measurements. Such a discrepancy already exists in the form of the Hubble tension, which may require new theoretical approaches to cosmic expansion (Jedamzik, Pogosian, & Zhao, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the most effective attempts of solutions to the Hubble tension are those that modify the cosmic expansion history at early epochs (see, e.g., Knox & Millea 2020;Schöneberg et al 2021), leading to a reduced sound horizon at recombination, it was shown that this change alone did not fully resolve the H 0 tension while remaining consistent with other cosmological datasets (Jedamzik et al 2021).…”
Section: Parametrizing the Eft Functionsmentioning
confidence: 99%